An Assessment of Parameters for Cementation of Impurities from Zinc Sulphate Leach Solution by a Statistical Design - Singh A.R.; Joseph A.S.; Rao M.D.; Singh K.K. (My University, 2025)
In this article, the cementation of major impurities from zinc sulphate leach solution by the addition of zinc dust was studied by considering different parameters including time, mesh size, and percentage of excess zinc dust. The output obtained from various experiments was utilized for the design of experiments. A multi-level categorical factorial design with a quadratic model was employed during this study. Results were predicted to minimize the concentration of impurity metals in the solution by altering the parameters. Furthermore, these predicted results were validated by performing another experiment. Successfully, it showed that the predicted and experimental data values were close to each other. The predicted optimized values were 40 min, 100% excess zinc dust, and 300 mesh size for copper; 42 min, 100% excess zinc dust, and 300 mesh size for cobalt; 37 min, 100% excess zinc dust, and 300 mesh size for cadmium; and 34 min, 100% excess zinc dust, and 300 mesh size zinc dust for nickel. At these optimized values, the experimental results showed 99.99%, 55.7%, 99.6%, and 76.6% cementation efficiencies for copper, cobalt, cadmium, and nickel respectively. The statistical design of experiments for the effective cementation of impurities corroborates the economic feasibility of optimizing parameters for the proposed process. © 2022, Society for Mining, Metallurgy & Exploration Inc.